Studies on the interaction of cholesterol analogues with cholesterol oxidising systems and membrane components - Craig, Iain F. (The University of Edinburgh, 1979)
A series of cholesterol analogues possessing side chains with either more or less carbon atoms than cholesterol were synthesised from hyodesoxycholic acid and fully characterised by nuclear magnetic resonance, mass spectrometry, and infra red analysis. These analogues were used in (a) physical studies of cholesterol phospholipid interactions and (b) experiments to investigate the substrate specificities of cholesterol 7a"hydroxylase from rat liver and the adrenal mitochondrial cholesterol side chain cleavage enzyme. (a) The physical properties of cholesterol and a series of cholesterol side chain analogues were investigated by incorporating them into liposomes prepared from lipid films containing the sterol and a series of saturated or unsaturated phospholipids in the required molar proportions. A series of spin labels (3-nitroxy octane, Tempo, 25 nitroxy cholestane, and 3 nitroxy cholestane) were incorporated into the sterol phospholipid liposomes and the effect of each analogue on each spin label mobility was observed. In addition the effect of each analogue on water permeability across the liposomal membrane was determined. The results of both sets of experiments showed that the cholesterol molecule with its iso-octane side chain was optimally adapted for maximal interaction with phospholipid. This specificity was not observed in monolayer studies of cholesterol phospholipid interactions. (b) The involvement of the cholesterol side chain in cholesterol oxidation by the liver microsomal enzyme, cholesterol 7a~hydroxylase was determined using an established assay based on the oxidation of added radioactive cholesterol. Using phenobarbitone pretreated rats it was shown that the metabolism of short side chain analogues was stimulated whereas 7a~hydroxylase activity was unaffected. Thus it is postulated that the side chain of cholesterol determines its metabolic fate and that the shorter side chain analogues are metabolised by the inducible hepatic drug metabolising enzyme system. A new G.L.C. assay which measures the production of 7a-hydroxy cholesterol from endogenous microsomal cholesterol has been developed and used to investigate the problem of substrate supply for the 7ahydroxylase enzyme. This involved the addition of cholesterol in detergents in sonicated and unsonicated liposomes containing different molar proportions of sterol and in organic solvents to a cholesterol depleted form of the enzyme. The involvement of a soluble protein isolated from the 100,000 x g supernatant of rat liver by ammonium sulphate fractionation, gel filtration and ion exchange chromatography has also been demonstrated. The molecular weight of the protein has been determined by S.D.S. polyacrylamide gel electrophoresis, and its means of action investigated. The cholesterol side chain cleavage enzyme of rat adrenal mitochondria has been shown to possess an absolute requirement for cholesterol as substrate by use of a radio-immuno-assay that measures pregnenolone production from the exogenous cholesterol side chain analogues. The results of both the physical measurements and the enzyme assays show that the side chain of cholesterol plays a major role in determining the extent of the interaction between cholesterol and phospholipids and the specificity of cholesterol protein interaction